Atrial fibrillation and cognitive impairment: mechanisms, influencing factors, and prospects - Huang, Li-Juan; Chen, Jian-Shu; Song, Yu-Zhe; Chang, Peng (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAtrial fibrillation (AF) is a prevalent cardiac arrhythmia and a significant contributor to cardioembolic stroke, a condition closely linked to cognitive decline. However, research reveals that AF itself is independently associated with an increased risk of cognitive impairment. This high incidence of cognitive decline in AF patients may result from various mechanisms, including reduced cerebral perfusion, microembolism, decreased cardiac output, and chronic inflammation.MethodsThis review synthesizes current evidence on the relationship between AF and cognitive impairment, examines underlying mechanisms of cognitive decline in AF, and explores the roles of AF type, treatment approaches, left atrial characteristics, and associated conditions in cognitive function outcomes.ResultsCognitive outcomes in AF are further influenced by a range of factors, such as left atrial structural parameters, AF type and duration, anticoagulation use, catheter ablation, comorbidities, age, and gender.DiscussionThe review highlights the complex interplay between AF and cognitive impairment, emphasizing the importance of understanding the various mechanisms and factors that contribute to cognitive decline in AF patients. By examining the roles of AF type, treatment approaches, left atrial characteristics, and associated conditions, this review provides insights into potential strategies for mitigating cognitive impairment in AF patients.